Advances and trends in geodesy, cartography and geoinformatics II : proceedings of the 11th International Scientific and Technical Conference on Geodesy, Cartography and Geoinformatics (GCG 2019), 10-13 September, 2019, Demänovská Dolina, Low Tatras, Slovakia /: proceedings of the 11th International Scientific and Technical Conference on Geodesy, Cartography and Geoinformatics (GCG 2019), 10-13 September, 2019, Demänovská Dolina, Low Tatras, Slovakia. ([2020]) - Unknown
No abstract available